2021
DOI: 10.3390/f12111523
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Masking Effects of Age Trends on the Correlations among Tree Ring Proxies

Abstract: Age-related trends are present in tree-ring widths (TRW), but their presence in tree rings isotope is debated. It is unclear how cambial age influences the relationships between TRW and isotopes. Tree-ring isotopes of alpine larch and cembran-pine trees showed only trends in the juvenile period (>100 years), which might mask the inter-relations between tree-ring proxies during cambial age. This work tries to unmask the age-trend influences by examining the correlations in TRW—stable isotopes with and withou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…This difference may be attributed to the strong post-eruption cooling that caused lower δD values of precipitation, which was more represented in the cembran pine than in the larch. In a previous work, we found that larch showed a higher correlation between oxygen and hydrogen isotope data than cembran pine [82]. We attributed the strongest signal in the cellulose δ 18 O to the impact of both temperature and precipitation, since the tropical eruptions not only have a cooling effect but also produce circulation feedbacks at a continental scale that cause distinct effects on regional precipitation patterns [9].…”
Section: Discussionmentioning
confidence: 66%
“…This difference may be attributed to the strong post-eruption cooling that caused lower δD values of precipitation, which was more represented in the cembran pine than in the larch. In a previous work, we found that larch showed a higher correlation between oxygen and hydrogen isotope data than cembran pine [82]. We attributed the strongest signal in the cellulose δ 18 O to the impact of both temperature and precipitation, since the tropical eruptions not only have a cooling effect but also produce circulation feedbacks at a continental scale that cause distinct effects on regional precipitation patterns [9].…”
Section: Discussionmentioning
confidence: 66%
“…The selection of core samples for calculating the annual growth of wood was carried out according to the standard method adopted in dendrochronology. Cameral processing of the obtained material and core counting were carried out on a semi-automatic LinTab 6 installation with TsapWin software [11,12]. The content of chemical elements of these soils was determined using an atomic emission spectrometer with inductively coupled plasma SPECTRO ARCOS (Germany).…”
Section: Methodsmentioning
confidence: 99%
“…The use of hydrogen isotopes (δ 2 H) in precipitation samples have been studied at a global scale and broadly correlate with mean global temperature (Dansgaard, 1964;Konecky et al, 2020). However, only few studies have examined the potential use δ 2 H in tree rings as a paleoenvironmental proxy (Roden et al, 2000;Hilasvuori, 2011;Voelker et al, 2014;Kimak and Leuenberger, 2015;Arosio et al, 2021;Lehmann et al, 2021;Schuler et al, 2022;Churakova Sidorova et al, 2022a). Recent studies showed that δ 2 H in tree-ring cellulose (δ 2 H trc ) is more than a temperature proxy and can contain information about biochemical processes related to photosynthesis and ecohydrological changes (Lehmann et al, 2021;Schuler et al, 2022).…”
Section: Introductionmentioning
confidence: 99%